Preparation of Biogas Made from Pineapple Waste with the Addition of Tofu Waste - Kuswari, Zeta; Dewi, Earlyna Sinthia; Muanah, Muanah; Muliatiningsih, Muliatiningsih (Protech Biosystems Journal, 2022)
One alternative energy source for making organic waste which can be renewed is pineapple waste and tofu waste. Biogas produced from these two materials is environmentally friendly so it does not disturb the environment. The purpose of this research was to determine the changes in temperature and pH that occurred during the formation of pressure and volume of biogas. The method used in this study was an experimental method using a completely randomized design (CRD). There are 4 treatments in this study, namely T1: pineapple waste; T2 : tofu liquid waste; T3 : addition of tofu solid waste; and T4 : addition of tofu liquid waste and tofu solid waste. The measurement results were then analyzed using analysis of variance (ANOVA). If significantly different results were found, a further test was carried out with BNJ. The results showed that the addition of tofu waste significantly affected the temperature, pH, pressure and volume of bioga. The average temperature for each treatment was 28oC, while the highest pH was 8.55. The highest pressure calculation results were found at T4 of 109.42 N/m2, while for the highest volume it was found at T4 of 0.000016642m3. Based on the description above, it can be concluded that the addition of tofu waste has a significant effect on the formation of biogas